The impact of economic policy uncertainty on the real exchange rate: Evidence from the UK - Moldovan, P.; Lagoa, S.; Mendes, D. (International Journal of Economics and Business Research, 2025)
The world economy has been punctuated by uncertainty in recent years, as a result of the 2008 subprime crisis, the European sovereign debt crisis, Brexit, and the 2016 US presidential elections, to mention but a few of the reasons. This study explores how the UK real exchange rate reacts to economic policy uncertainty (EPU) shocks using monthly data for the period 1998 to 2020. We contribute to the literature by identifying the long-run and short-run impacts of EPU using a cointegrated ARDL model, and by studying a country that has been through periods of both relatively low and high uncertainty. Results confirm that EPU has an important effect in the long run by depreciating the exchange rate. In addition to urging policymakers and regulators to keep policy uncertainty to a minimum as a way of sustaining exchange rate stability and thus promoting long-term economic growth, further evidence is provided on exchange rate fundamentals.